Mineral lick visitation by bats : a study in Bornean tropical rainforest, Deramakot forestry district, Sabah - Lawrence Alan Bansa (2016)
Bats, like many terrestrial animals are attracted to visit and use mineral licks to meet their nutritional requirements. Although the importance of natural mineral licks for terrestrial animals is widely acknowledged, few studies have been done on natural mineral licks visitation on the bat fauna, particularly in Borneo and Southeast Asia in general. It is not known what species of bats frequently using mineral licks, and their daily temporal visitation pattern. Furthermore, it is not known how habitat disturbance affects the natural licks and how this in turn affects the bats behaviour and their persistence. A study on visitation of bats to mineral licks was conducted at eight sites within Deramakot Forest Reserve and Tangkulap Forest Reserve located in central part of Sabah, Malaysia, Northern Borneo. The sampling sites include six natural mineral licks and two other sites serving as control treatments. The specific objectives of the study were to determine the bat species richness and community assemblages at mineral licks, to determine the temporal pattern of bat visitation to mineral licks and visitation behaviours of bats at mineral licks. The main findings of the present study revealed that Palaeotropical frugivorous bats using mineral licks, specifically five species of common frugivorous bats. There was low evidence to support that insectivorous bats were the significant user to mineral licks based on the lower species occurrence at mineral lick and lower concentration of earthly materials, Al and Si at their faeces. Most of the frugivorous bats caught at mineral licks were reproductively inactive females compared to reproductively active females, with domination of post-lactating female bats. This study found that more bats actively visited mineral licks after the peak of their foraging activity (1800-2000h), at range 2200-0600h. Visitation of frugivorous bats was affected more by the human disturbances and structures of mineral lick puddles rather than concentrations of mineral contents in the water at mineral licks. Frugivorous bats were directly observed swiftly drinking from mineral licks (n=9). Observation of bats using licks showed two identified behaviours: A. Drink on the wing; B. Cling and drink. This drinking behaviours showed in a short period of time (less than 30 sec. appx.).In conclusion, results of present study demonstrated that frugivorous bats using mineral licks with domination by female bats as their visiting pattern peaked after peak of foraging period and visiting behaviours to mineral licks is affected by human disturbances. Mineral licks are important features in the forest and should be managed as part of the conservation strategies for bats population.